2010
DOI: 10.1016/j.vaccine.2010.03.062
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of low-dose recombinant human interferons α-2b nasal spray to prevent acute viral respiratory infections in military recruits

Abstract: The military population has a high disease burden of acute viral respiratory infections in China. To assess the efficacy and safety of a low-dose recombinant human interferon alpha-2b (rIFNalpha-2b) nasal spray in preventing acute viral respiratory infections in military population, we performed this randomized controlled trial. The results showed that application of the rIFNalpha-2b nasal spray had the benefits in prevention of infections caused by influenza A virus, influenza B virus parainfluenza viruses 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 25 publications
0
39
0
3
Order By: Relevance
“…Indeed, this diagnostic and therapeutic approach began shortly after the discovery of IFN 62 . Since that time, some studies showed that IFN induction or administration might reduce respiratory viral infection 63-66 whereas other studies found no effect in otherwise healthy subjects 67 or in those with chronic respiratory disease 68 . Presumably, this data on efficacy and associated side effects underlies the fact that IFN treatment is not generally used for antiviral therapy and fits with the idea that endogenous IFN production is already optimal in most individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this diagnostic and therapeutic approach began shortly after the discovery of IFN 62 . Since that time, some studies showed that IFN induction or administration might reduce respiratory viral infection 63-66 whereas other studies found no effect in otherwise healthy subjects 67 or in those with chronic respiratory disease 68 . Presumably, this data on efficacy and associated side effects underlies the fact that IFN treatment is not generally used for antiviral therapy and fits with the idea that endogenous IFN production is already optimal in most individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Serum IgM levels were measured as evidence of virus infection. Subjects receiving rIFN-a had lower concentrations of serum IgM specific for H3N2 influenza A virus, influenza B virus, adenovirus (species B), and parainfluenza virus types 1, 2 and 3 [52]. Specifically with regard to influenza A virus, only 30 recruits treated with rIFN-a had detectable levels of influenza A virus IgM compared with 104 recruits in the untreated control group [52].…”
Section: Ifn Therapy For Influenza a Virus Infectionsmentioning
confidence: 97%
“…A recently completed randomized controlled trial has examined the safety and efficacy of recombinant IFN-a (rIFN-a) treatment, administered in the form of a nasal spray, in military recruits, in the context of protection from respiratory virus infections [52]. Serum IgM levels were measured as evidence of virus infection.…”
Section: Ifn Therapy For Influenza a Virus Infectionsmentioning
confidence: 99%
“…LuLu Gao и соавт. [18], продемонстрировав возмож-ность предупреждения ОРВИ у взрослых профилак-тическим применением низких доз рекомбинантно-го назального аэрозоля человеческого интерферона альфа-2b, показали, что препарат топический IFN-α более эффективно предупреждает развитие инфек-ций, вызванных вирусами гриппа и аденовирусами, чем респираторно-синцитиальным вирусом.…”
Section: вирусunclassified